POLA PENGGUNAAN BAHASA GURU ( ALIH KODE DAN CAMPUR KODE) DALAM PEMBELAJARAN BAHASA JERMAN PADA SMA PGRI 1 AMBON DAN SMA NEG 10 AMBON - Apituley, Patresia Silvana; Tuhumury, Fin Rosa (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This study aims to examine the language use patterns of teachers in teaching German, focusing on the phenomena of code-mixing and code-switching. In the context of foreign language learning in Indonesia, the use of more than one language is a common strategy employed by teachers to bridge students’ understanding of the material. This research employs a descriptive qualitative approach, with data collected through observation, interviews, field notes, and literature review. The findings reveal that during the opening and closing phases of the lesson, teachers tend to use code-switching from German to Indonesian to provide clearer explanations or instructions. Meanwhile, during the core teaching phase, teachers frequently apply code-mixing by inserting German or English vocabulary or phrases into Indonesian sentences. These results align with the theory of translanguaging (García & Wei, 2014), which emphasizes the flexible use of multiple languages to enhance student comprehension. Therefore, the use of code-mixing and code-switching in German language instruction can be considered an effective pedagogical strategy when used intentionally and proportionally.